Leading the Party: Coordination, Direction, and Communication. - Dewan, T; Myatt, D (2007)
Party activists face a coordination problem: a critical mass--a barrier to coordination--must advocate a single policy alternative if the party is to succeed. The need for direction is the degree to which the merits of the alternatives respond to the underlying fundamentals of the party's environment. An individual's ability to assess the fundamentals is his sense of direction. These three factors--the barriers to coordination, the need for direction, and an individual's sense of direction--combine to form an index of both the desirability and the feasibility of leadership. We offer insights into Michels' Iron Law: a sovereign party conference gives way to leadership by an individual or oligarchy if and only if the leadership index is sufficiently high. Leadership enhances the clarity of intraparty communication, but weakens the response of policy choices to the party's environment. Our model can also be applied to the coordination problems faced by instrumental voters in plurality-rule elections, and so relates to the psychological effect of Duverger's Law.